Internationalizing circular economy companies : Finnish SMEs in focus - Maste, Teemu (My University, 2024)
As the Earth's carrying capacity and resources continue to decrease, the linear economic model is coming to its end. Circular economy (CE), where materials are kept in circulation much longer and waste generation is minimized, offers a sustainable alternative to the traditional linear economy. With CE, at its best, it is possible to achieve the decoupling of economic growth from excessive use of natural resources. CE has already grown significantly in recent years, especially in the EU area but there is still a strong global growth potential in CE as it continues to grow and replace the traditional linear economy worldwide. As Finland is a small country with a small domestic market, the key to significant growth can only be found in international markets. Even though Finland has traditionally been a technologically advanced and innovative country, statistically Finland's CE figures are not even at the level of the EU average. But, looking beyond statistics there is a significant amount of potential for the international success of the Finnish CE industry. The purpose and goal of this study is to understand the opportunities for Finnish CE companies to grow internationally and to provide possible solutions for Finnish CE companies to successfully internationalize their operations. Existing literature of CE has focused on various circular economy business models (CEBMs) and CE ecosystems. The role and significance of CE ecosystems becomes particularly important when viewed from the perspective of an internationalizing company. Successful internationalization emphasizes the utilization of networks and the significance of the institutional environment. Both of these factors are also highly emphasized in the success of CE ecosystems. This research aims to find ways for Finnish CE companies to utilize ecosystems in their internationalization efforts. The empirical findings of the study were collected by interviewing Finnish CE companies, each representing a specific CEBM. Interviews were conducted to ensure representation of all different CEBMs to provide a comprehensive picture of the Finnish CE industry as a whole. The interviews were conducted as theme interviews, which were aligned with the research questions and the theoretical framework. The interviews were transcribed carefully, and the interview material was analysed thematically. The empirical results of the study confirmed several observations from the literature, such as the significance of ecosystems in the internationalization of CE companies, and especially the importance of partners and financing when entering new markets. However, the significance of financing was much more emphasized in the empirical data of the study compared to the literature, as was the variability in how successfully CE companies were able to utilize partners. The interviews also emphasized the importance of the home CE ecosystem more than the literature; Finland's business environment significantly influences the opportunities for Finnish CE companies to achieve international growth. This study identified the different challenges and opportunities Finnish CE companies face in the international markets and eventually offered implications for various stakeholders of the Finnish CE ecosystem that could accelerate the international growth of the whole Finnish CE industry.

Maapallon kantokyvyn ja resurssien jatkuvasti huvetessa on lineaarinen talousmalli tulossa tiensä päähän. Kiertotalous, jossa materiaalit saadaan pidettyä huomattavasti pidempään kierrossa ja jätteen määrä vähäisempänä, on tarjoamassa kestävän vaihtoehdon perinteiselle lineaariselle taloudelle ja mahdollistamassa taloudellisen kasvun ja luonnonvarojen liikakäytön irtikytkennän. Kiertotalous on kasvanut viime vuosina etenkin EU-alueella ja kasvupotentiaalia on merkittävästi vielä edessä, kun globaali talous siirtyy vähitellen lineaarisesta mallista kiertoon. Suomen ollessa pieni valtio ja markkina on kasvun avaimet löydettävä kansainvälisiltä markkinoilta. Suomi on perinteisesti ollut teknologisesti edistyksellinen maa, jossa uusia innovaatioita syntyy vilkasta tahtia. Kuitenkin tilastojen valossa Suomen kiertotalousluvut eivät ole edes EU:n keskitasoa. Tilastojen taakse katsoessa pystyy tästä huolimatta näkemään myös suuren määrän potentiaalia suomalaisen kiertotalouskentän kansainväliselle menestykselle. Tämän tutkielman tarkoituksena ja tavoitteena on ymmärtää suomalaisten kiertotalousyritysten mahdollisuudet kansainväliseen kasvuun ja antaa onnistumisen avaimia kansainvälistyville suomalaisille kiertotalousyrityksille. Kiertotalouteen liittyvä kirjallisuus on keskittynyt pitkälti kiertotalouden erilaisiin liiketoimintamalleihin sekä kiertotalousekosysteemeihin. Kiertotalousekosysteemien rooli ja merkitys nousee erityisen tärkeäksi, kun asiaa tarkastellaan kansainvälistyvän yrityksen näkökulmasta. Onnistuneessa kansainvälistymisessä korostuu verkostojen hyödyntäminen sekä institutionaalisen ympäristön merkitys. Nämä molemmat muuttujat korostuvat myös erityisen paljon kiertotalousekosysteemien toimivuudessa. Tämä tutkimus pyrkiikin löytämään suomalaisille kiertotalousyrityksille tapoja hyödyntää kiertotalousekosysteemejä kansainvälistymisessä. Tutkimuksen empiiriset löydökset kerättiin haastattelemalla suomalaisia kiertotalousyhtiöitä, jotka edustivat kukin tiettyä kiertotalouden liiketoimintamallia. Haastatteluita tehtiin sen verran, että kaikki kiertotalouden eri liiketoimintamallit olivat edustettuina, jotta saatiin kattava kuva suomalaisesta kiertotalouskentästä kokonaisuutena. Haastattelut toteutettiin teemahaastatteluina, joissa teemat muodostuivat tutkimuskysymysten ja teoreettisen viitekehyksen mukaan. Haastattelut litteroitiin huolellisesti ja haastatteluaineisto analysoitiin teemoittain. Tutkimuksen empiiriset tulokset vahvistivat useita kirjallisuudesta nousseita havaintoja, kuten ekosysteemin kokonaisvaltaisen merkityksen kansainvälistymisessä, sekä erityisesti kumppaneiden ja rahoituksen tärkeyden uusille markkinoille mentäessä. Rahoituksen merkitys oli kuitenkin tutkimuksen empiriassa huomattavasti enemmän korostunut, kun kirjallisuudessa, kuten oli myös vaihtelevuus kumppaneiden onnistuneessa hyödyntämisessä. Haastatteluissa korostui myös kirjallisuutta enemmän kotimaisen kiertotalousekosysteemin merkitys; Suomen liiketoimintaympäristö vaikuttaa olennaisesti siihen, millaiset kansainvälisen kasvun eväät suomalaisten yritysten on mahdollista saada. Tämä tutkimus onnistui ennen kaikkea tunnistamaan suomalaisten kiertotalousyritysten kansainvälistymiseen liittyvät haasteet ja mahdollisuudet, ja sitä kautta luomaan konkreettisia suosituksia kansainvälistyville suomalaisille kiertotalousyrityksille sekä muille kiertotalousekosysteemin osapuolille.
Keywords: circular economy, ecosystems, institutions, networks, Finland, internationalization